2019
DOI: 10.1088/1757-899x/624/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design and Analyses of T-shaped rotor Magnetorheological Brake

Abstract: Magnetorheological (MR) brakes, belonging to the class of electromagnetic brakes, have a potential to replace conventional hydraulic brakes owing to reversible, rapidly controllable torque characteristics. In this study, T-shaped rotor MR brake was considered due to their higher braking torque capability and compactness compared to other configurations of brake. Optimal design of the brake was performed considering brake rotor radius, rotor thickness, flange length, casing thickness, coil height and coil width… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Le-Duc et al [12] optimized the MRB to maximize the braking torque and minimize the mass using the non-dominated sorting GA and a robust multi-objective optimization method combined with finite element analysis. Axharya et al [13] fully considered factors such as the brake radius, rotor thickness, shell thickness, coil height, and width in the optimal design of a T-type rotor MRB to obtain the maximum torque ratio and minimum brake mass.…”
Section: Introductionmentioning
confidence: 99%
“…Le-Duc et al [12] optimized the MRB to maximize the braking torque and minimize the mass using the non-dominated sorting GA and a robust multi-objective optimization method combined with finite element analysis. Axharya et al [13] fully considered factors such as the brake radius, rotor thickness, shell thickness, coil height, and width in the optimal design of a T-type rotor MRB to obtain the maximum torque ratio and minimum brake mass.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, a large number of magneto-rheological brake (MRB) configurations have been proposed to improve their braking torque, compact size or mass and power consumption [17][18][19][20][21][22][23][24][25][26][27][28][29]. The original and well-known configuration of MRB is the disc-type [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the disc type MRB, at the same value of maximum achievable braking torque, the mass of drum-type MRB is significantly greater than that of the disc-type [23]. The MRB with T-shaped rotor configuration, a combination of drum-type and disc type, was proposed taking advantages from both the disc-type and the drum type [24,25]. It was shown that, at the same constrained space, the braking torque of the T-shaped rotor MRB was considerably higher than that of the drum-type.…”
Section: Introductionmentioning
confidence: 99%
“…By optimal design, performance of the hybrid type MRB can be significantly improved, especially in case the available working space is a long, large cylinder [12,13]. To increase the torqueto-mass ratio of the hybrid-type MRB, MRBs with T-shaped rotor (T-shaped rotor MRB) were developed [14,15]. In the T-shaped rotor MRB, two mutual magnetic coils are placed on the side housings at two ends of the T-shaped rotor flange.…”
Section: Introductionmentioning
confidence: 99%